Shock Therapy : A History of Electroconvulsive Treatment in Mental Illness - Shorter, Edward (Book collections on Project MUSE., 2013)
Edward Shorter and David Healy trace the controversial history of ECT and other ""shock"" therapies. Drawing on case studies, public debates, extensive interviews, and archival research, the authors expose the myths about ECT that have proliferated over the years. By showing ECT's often life-saving results, Shorter and Healy endorse a point of view that is hotly contested in professional circles and in public debates, but for the nearly half of all clinically depressed patients who do not respond to drugs, this book brings much needed hope.